Commonalities and differences in injured patient experiences of accessing and receiving quality injury care: a qualitative study in three sub-Saharan African countries - Antonio Belli; Justine Davies; Stephen Tabiri; John Whitaker; Maria Lisa Odland; Anthony Howard; Abebe Bekele; Agnieszka Ignatowicz; Kathryn M Chu; Abdul-Malik Abdul-Latif; Karen Ferreira; Pascal Nzasabimana; et al. (BMJ Open)
Objectives To understand commonalities and differences in injured patient experiences of accessing and receiving quality injury care across three lower-income and middle-income countries.Design A qualitative interview study. The interviews were audiorecorded, transcribed and thematically analysed.Setting Urban and rural settings in Ghana, South Africa and Rwanda.Participants 59 patients with musculoskeletal injuries.Results We found five common barriers and six common facilitators to injured patient experiences of accessing and receiving high-quality injury care. The barriers encompassed issues such as service and treatment availability, transportation challenges, apathetic care, individual financial scarcity and inadequate health insurance coverage, alongside low health literacy and information provision. Facilitators included effective information giving and informed consent practices, access to health insurance, improved health literacy, empathetic and responsive care, comprehensive multidisciplinary management and discharge planning, as well as both informal and formal transportation options including ambulance services. These barriers and facilitators were prevalent and shared across at least two countries but demonstrated intercountry and intracountry (between urbanity and rurality) variation in thematic frequency.Conclusion There are universal factors influencing patient experiences of accessing and receiving care, independent of the context or healthcare system. It is important to recognise and understand these barriers and facilitators to inform policy decisions and develop transferable interventions aimed at enhancing the quality of injury care in sub-Saharan African nations.